Mechanical properties of concrete with clam shell powder (csp) as partial cement replacement - Mahshuri, Yusof; Sinin, Hamdan; Sinin, Aaliyawani Ezzerin (Scientific.Net, 2023)
This research focuses on compressive strength of concrete containing different percentages of municipal waste clam shell powder (CSP). The amount of cement is replaced by 5%, 10% and 15% of CSP. The result obtained shows that the compressive strength increases with the CSP content. Concrete containing 15%CSP has lower compressive strength compared to those containing 5% and 10%CSP. The concrete containing 15%CSP is almost similar to the control concrete (with zero CSP).